Galvanotactic directionality of cell groups depends on group size - Calina Copos; Yao-Hui Sun; Kan Zhu; Yan Zhang; Brian Reid; Bruce Draper; Francis Lin; Haicen Yue; Yelena Bernadskaya; Min Zhao; Alex Mogilner (Proceedings of the National Academy of Sciences, 2025)
Motile cells migrate directionally in the electric field (EF) in a process known as galvanotaxis, an important phenomenon in wound healing and development. We previously reported that individual fish keratocyte cells migrate to the cathode in EFs, that inhibition of PI3 kinase (PI3K) reverses single cells to the anode, and that large cohesive groups of either unperturbed or PI3K-inhibited cells migrate to the cathode. Here, we report that small uninhibited cell groups move to the cathode, while small groups of PI3K-inhibited cells move to the anode. Small groups move faster than large groups, and groups of unperturbed cells move faster than PI3K-inhibited cell groups of comparable sizes. The shapes and sizes of large groups change little when they start migrating, while size and shapes of small groups change significantly, and lamellipodia disappear from the rear edges of these groups. The computational model, according to which cells inside and at the edge of the group interpret directional signals differently, explains the observations. Namely, cells in the group interior are directed to the cathode independently whether they are PI3K-inhibited or not. Meanwhile, the edge cells behave like individual cells: They are directed to the cathode in uninhibited groups and to the anode in PI3K-inhibited groups. As a result, all cells drive uninhibited groups to the cathode, while larger PI3K-inhibited groups are directed by cell majority in the group interior to the cathode, while majority of the edge cells in small groups win the tug-of-war driving these groups to the anode.